2014
DOI: 10.3400/avd.ra.14-00048
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Vascular Function and the Autonomic Nervous System

Abstract: Endothelial dysfunction and autonomic nervous system dysfunction are both risk factors for atherosclerosis. There is evidence demonstrating that there is a close interrelationship between these two systems. In hypertension, endothelial dysfunction affects the pathologic process through autonomic nervous pathways, and the pathophysiological process of autonomic neuropathy in diabetes mellitus is closely related with vascular function. However, detailed mechanisms of this interrelationship have not been clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 102 publications
(89 reference statements)
1
85
0
5
Order By: Relevance
“…In diverse contexts, both experimental and clinical, persistent sympathetic nervous system activations have been causally linked to cardiovascular damage, to endothelial dysfunction, 46 to the development of left ventricular hypertrophy, 47 to atherosclerosis development 48 and to atrial and ventricular arrhythmias. 19,49,50 Single Sympathetic Nerve Firing Salvos Direct recording from the human cardiac sympathetic nerves is not possible, but the presence there of multiple firing salvos is probable, as patients who have nerve firing salvos recorded at microneurography have, in parallel, the highest levels of cardiac norepinephrine spillover.…”
Section: Potential Neural Mechanisms Of Toxicity Of the Sympathetic Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In diverse contexts, both experimental and clinical, persistent sympathetic nervous system activations have been causally linked to cardiovascular damage, to endothelial dysfunction, 46 to the development of left ventricular hypertrophy, 47 to atherosclerosis development 48 and to atrial and ventricular arrhythmias. 19,49,50 Single Sympathetic Nerve Firing Salvos Direct recording from the human cardiac sympathetic nerves is not possible, but the presence there of multiple firing salvos is probable, as patients who have nerve firing salvos recorded at microneurography have, in parallel, the highest levels of cardiac norepinephrine spillover.…”
Section: Potential Neural Mechanisms Of Toxicity Of the Sympathetic Pmentioning
confidence: 99%
“…• Endothelial damage (88)(89)(90)(91) • Atherogenesis (48,(94)(95)(96) • Left ventricular hypertrophy (46,97) • Atrial and ventricular cardiac arrhythmias (48,54) • Thrombogenesis in myocardial infarction and stroke (99) Excess Clinical Cardiovascular Endpoints (5,14)…”
Section: Mechanisms Of Cardiovascular Toxicitymentioning
confidence: 99%
“…Thus, cytokines, chemokines and growth factors seem to play a significant part in the inflammatory process (14,15). However, Amiya et al in 2014 indicated that vascular function could also be impaired from alterations in the autonomic nervous system (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, convincing evidence suggests that endothelial dysfunction plays an essential role in the pathophysiology of β-adrenoreceptor activation [17][18][19], providing a link between endothelial dysfunction and β-adrenoreceptor responsiveness. Accordingly, we designed a study to evaluate whether FMD could be used as a sensitive marker to predict the IDC patient's response to β-blocker therapy and LV reverse remodeling.…”
Section: Accepted Manuscriptmentioning
confidence: 99%